2017
DOI: 10.1121/1.5010064
|View full text |Cite
|
Sign up to set email alerts
|

Ship localization in Santa Barbara Channel using machine learning classifiers

Abstract: Machine learning classifiers are shown to outperform conventional matched field processing for a deep water (600 m depth) ocean acoustic-based ship range estimation problem in the Santa Barbara Channel Experiment when limited environmental information is known. Recordings of three different ships of opportunity on a vertical array were used as training and test data for the feed-forward neural network and support vector machine classifiers, demonstrating the feasibility of machine learning methods to locate un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 128 publications
(28 citation statements)
references
References 13 publications
1
27
0
Order By: Relevance
“…Recent interest in ML first appeared for target classification. 42,172 Studies of ocean source localization using ML appeared soon thereafter, 4,152 including applications to experimental data for broadband ship localization, 151 and target characterization. 173 Recently, studies have examined underwater source localization with CNNs 174 and DL, 175,176 taking advantage of 2D data structure, shared weighting, and huge modelgenerated datasets.…”
Section: Source Localization In Ocean Acousticsmentioning
confidence: 99%
“…Recent interest in ML first appeared for target classification. 42,172 Studies of ocean source localization using ML appeared soon thereafter, 4,152 including applications to experimental data for broadband ship localization, 151 and target characterization. 173 Recently, studies have examined underwater source localization with CNNs 174 and DL, 175,176 taking advantage of 2D data structure, shared weighting, and huge modelgenerated datasets.…”
Section: Source Localization In Ocean Acousticsmentioning
confidence: 99%
“…They used the group method of data handling (GMDH) neural networks and an adaptive network-based fuzzy inference system (ANFIS) with good results. Niu et al [26] used the feed-forward neural network (FFNN) and support vector machine (SVM) classifiers to infer ship location from acoustical data in a deep waterway channel. Bannari et al [27] suggested an approach for bathymetric mapping of shallow water of Arabian Gulf near Bahrain using the kriging procedure.…”
Section: Related Workmentioning
confidence: 99%
“…Most recent machine learning methods are data-hungry and the successful applications can be found especially in image processing, which is largely driven by the recently openly available huge volume of image datasets that could consist of millions of items [29]. In acoustic studies, most recent works have been primarily focused on acoustic signal processing [30][31][32][33] partly due to the presumed analogy with the imaging processing applications. To study new problems, the corresponding datasets should be prepared in advance to enable machine learning.…”
Section: Introductionmentioning
confidence: 99%